THE QUALITY OF WELL WATER IN THE SPRUZEVA VILLAGE - Zeļča, Jūlija; Teirumnieka, Ērika (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
The article contains information on the water quality of Spruzeva village wells, which was determined by chemical and microbiological indicators. Methods of detection have been described. The analysis of the obtained chemical and microbiological research results and comparison with the drinking water quality targets were carried out. Since microbiological and chemical contamination has been detected in the studied wells, proposals have been made to improve water quality.